Assessing barriers for delayed antenatal care services among tribal women of Bangladesh - Karim, A.N.M. Rezaul (Penerbit Universiti Kebangsaan Malaysia, 2019)
Introduction The time to start Antenatal Care (ANC) check-up is very significant because it determines the way to resolve complications and remedies during pregnancy. Different parameters play important roles in participating ANC in a society. A global consensus gives us the idea that most tribal people living in remote areas are far from basic needs related to education, employment, and affordable healthcare. The study aimed to delve into delayed ANC practices and the factors affecting the decision to receive ANC among tribal women dwelling in the Chittagong Hill Tracts (CHT) of Bangladesh. Methods This paper is a quantitative study. Interview schedule or questionnaire was mainly used as an instrument for data collection from 556 married women having babies for less than one year. Multinomial logistic regression was performed to determine significant factors related to the time of the introduction of ANC. Results Only 16.4% of the women had started to receive ANC in the early stage of pregnancy (≤3 months) and 13.5%, after three months (delayed ANC) of their pregnancies. 70% did not seek ANC. The result found that one-third (29.9%) of the pregnant women wanted ANC from a trained doctor, but only 16.4% initiated attendance within three months of the pregnancy. Conclusions The study results suggest that specific efforts are needed to advance the socio-economic status of the tribal people; they need to increase the educational level of women and their husbands, build their nearest health centers, and strengthen family planning programs.